Ecocriticism and Italy Ecology, Resistance, and Liberation - Iovino, Serenella (Environmental Cultures, 2016)
Winner of the MLA Aldo and Jeanne Scaglione Prize for Italian Studies 2016 Winner of the American Association for Italian Studies Book Prize 2016 This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Written by one of Europe's leading critics, Ecocriticism and Italy reads the diverse landscapes of Italy in the cultural imagination. From death in Venice as a literary trope and petrochemical curse, through the volcanoes of Naples to wine, food and environmental violence in Piedmont, Serenella Iovino explores Italy as a text where ecology and imagination meet. Examining cases where justice, society and politics interlace with stories of land and life, pollution and redemption, the book argues that literature, art and criticism are able to transform the unexpressed voices of these suffering worlds into stories of resistance and practices of liberation.